Penerapan Nilai-Nilai Haji Dari Hadis Nabi dalam Konteks Globalisasi - Idris Siregar; Nurul Hasanah Simamora; Nur Syahri Siregar (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
The purpose of this research was to understand how the values of Hajj, as contained in the hadiths of the Prophet, were applied in the context of globalization. The research method used was a type of library research or literature study, which involved collecting, reading, noting, and processing data from various literary sources such as books, magazines, and others. The results of the research indicated that the application of Hajj values from the Prophet's hadiths in the context of globalization required awareness and a collective commitment from Muslims and all humanity. By using the values of Hajj as a foundation in human interactions and in building a more just, harmonious, and sustainable global society, we could create a better world for future generations. The Hajj values derived from the hadiths of Prophet Muhammad (PBUH) taught universal principles that were highly relevant in the context of globalization. Equality, brotherhood, peace, togetherness, solidarity, obedience, devotion, patience, sacrifice, sincerity, and honesty were values that could help humanity overcome global challenges and create a more just, peaceful, and sustainable world.